Biomechanical Evaluation of the Suitability of Monofilament Nylon Fishing and Leader Line for Extra-articular Stabilisation of the Canine Cruciate-deficient Stifle - Caporn, T. M.; Roe, S. C. (Veterinary and Comparative Orthopaedics and Traumatology, 1996)
The use of monofilament nylon line for extra-articular stabilisation of the cruciate deficient canine stifle is widespread in veterinary surgery. The purpose of this study was twofold: 1) to examine the mechanical behaviour of two forms of monofilament line - standard nylon fishing line (NFL) and nylon leader line (NLL) - when sterilised by steam or ethylene oxide and formed into loops approximating their use in the clinical situation; 2) to compare the mechanical performance of the canine fabellar attachment site to the steel hooks used in the first part of the study.It was found that NLL loops were not affected by sterilisation and had higher failure loads and stiffness than NFL loops. Further testing of 27-kilo - gram-test (kgt) and 36 kgt steam-sterilised NFL and NLL found that of the materials tested, NLL 27 kgt was most suitable as an extra-articular stabiliser of the canine stifle. The performance of the fabellar attachment site was superior to the steel hooks when cycled to 50 N and inferior when cycled to 100 N.The suitability of monofilament nylon fishing line (NFL) and monofilament nylon leader line (NLL) for use as lateral fabel-lotibial sutures (LFTS) in canine cranial cruciate ligament repair was investigated. In vitro testing of loops of the materials was performed with steel hook and fabellar attachment points. Twenty-seven-kilogram test NLL was found to be the most suitable nylon line from which to construct an LFTS.
Keywords: Cranial cruciate ligament; monofilament nylon; material properties; biomechanics